Phytochemical Analysis and antimicrobial activity of Five medicinal plants from Libya (Journal of Academic Research, 2025)
The phytochemical profile and antimicrobial effectiveness of five native Libyan medicinal plants—Ephedra foeminea, Plantago uniflora, Ammi visnaga, Angelica polymorpha var. sinensis, and Tirmania species—are investigated in this study. The Soxhlet apparatus was used to extract plant components both aqueously and ethanolically. Numerous bioactive substances, with varying compositions among extract types, were found through qualitative phytochemical screening. These included Flavonoids, Alkaloids, Carbohydrates, Saponins, Cardiac, Glycosides, Coumarins, Tannins, Phenols, Proteins , Terpenoids and Resins. The extracts had mild acidity, with pH values ranging from 5.39 to 6.20. Staphylococcus aureus, Escherichia coli, Acinetobacter species and Staph aureus were among the Gram-positive and Gram-negative bacteria against which antibacterial activity was evaluated using the disk diffusion method. Significant inhibitory effects were shown by both ethanolic and aqueous extracts, especially against Streptococcus and E. coli, indicating potential for therapeutic uses.In addition to demonstrating the usefulness of Libyan flora as a source of innovative antibacterial agents, the diversity and richness of phytochemicals found in these species support their historic usage in ethnomedicine and highlight their pharmaceutical potential.
Keywords: Phytochemical screening; Medicinal plants; Antibacterial activity; Inhibition zone; Libyan flora